Cambridge grammar of English : a comprehensive guide : spoken and written English grammar and usage - Carter, Ronald, 1947- (Cambridge University Press, 2006)
A major reference grammar offering the most comprehensive and up-to-date coverage of spoken and written English based on real everyday usage. The Cambridge Grammar of English is a major reference grammar from the world's leading grammar publisher. Using ground breaking language research, it offers clear explanations of spoken and written English based on real everyday usage. A clear two-part structure makes the book particularly user-friendly. In the first section, A-Z entries give more attention to lexico-grammar and other language areas that tend to be neglected in grammar references. The second section covers traditional grammatical categories such as tense, clause structure and parts of speech.